Job Performance dan Job Satisfaction Wartawan Sebagai Dampak Job Stress Di Masa Pandemi COVID-19 - Dian Agustina; Dita Oki Berliyanti; Ida Ariyani (Faculty of Economics and Business University of Lampung, 2022)
This study aimed to analyze the effect of job stress on job performance and job satisfaction by mediating work engagement. This study uses Job Stress as the independent variable, Job Performance and Job Satisfaction as the dependent variables, and Work Engagement as the mediating variable. Data collection from 311 print and online media journalists in Jakarta. The data collection technique in this study used purposive sampling, and the research instrument used a questionnaire sent via Google Form. Data analysis using the Structural Equation Model (SEM) AMOS 22 method. The results show a positive and significant effect of job stress on work engagement but negatively affects job performance and insignificant job satisfaction. Work engagement has a positive effect on job performance and job satisfaction. The results of this study are to maintain the effect of Job Stress on Job Performance and Job Satisfaction mediated by Work Engagement on journalists in Jakarta due to the implementation of the WFH policy as a result of the COVID-19 pandemic. Abstrak Tujuan penelitian ini adalah untuk menganalisis pengaruh job stress terhadap job performance dan job satisfaction dengan mediasi work engagement. Penelitian ini menggunakan Job Stress sebagai variabel bebas, Job Performance dan Job Satisfaction sebagai variabel terikat, dan Work Engagement sebagai variabel mediasi. Data dikumpulkan dari 311 responden yang merupakan wartawan di media cetak dan online yang bekerja di Jakarta. Teknik pengambilan data dalam penelitian ini menggunakan purposive sampling dan instrumen penelitian menggunakan kuesioner yang dikirimkan melalui Google Form. Analisis data dilakukan dengan metode Structural Equation Model (SEM) AMOS 22. Hasil penelitian menunjukkan terdapat pengaruh positif dan signifikan job stress terhadap work engagement tetapi berpengaruh negative terhadap job performance dan tidak signifikan terhadap job satisfaction, terdapat pengaruh positif dan signifikan work engagement terhadap job performance. Work engagement berpengaruh posisit fan terhadap job satisfaction dan job satisfaction. Hasil penelitian ini yaitu untuk dapat mempertahankan pengaruh Job Stress terhadap Job Performance dan Job Satisfaction yang dimediasi Work Engagement pada wartawan di Jakarta akibat penerapan kebijakan WFH sebagai dampak pandemi COVID-19. Kata Kunci: Job Stress, Job Performance, Job Satisfaction, Work Engagement